Analisis Sentimen Program Makan Bergizi Gratis pada Podcast Bocor Alus Politik dengan Algoritma Naive Bayes - Tuasamu, Abdulrahman; Gumilang, Rapanca Cahya; Fachrian, Mohammad Akmal; Krisnandi, Daiva Rakha; Indryani, Azizah Wardah; Hasan, Fuad Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Free Nutritious Meal (MBG) program initiated by the elected administration has evolved into a strategic public policy, yet it has garnered diverse responses from various strata of society. These opinion dynamics are clearly evident through the high volume of interaction on social media, particularly within the comment section of the